DAYA TERIMA, KADAR PROTEIN, KADAR LIPID DAN JUMLAH MIKROBA PADA KEFIR SUSU SAPI DAN KEFIR SUSU KAMBING SEBAGAI ALTERNATIF MINUMAN PROBIOTIK - Istawa, Ratu Ayu; Fajri, Roifah; Arifin, Dedi Zaenal (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2018)
Background: In Indonesia, indigestion issue specifically diarrhe was 6,897,463 cases in 2006. One of the factors causing indigestion issue is food intake. An alternative to prevent digestive problems is consumption of functional foods such as probiotic drink i.e. kefir. Kefir is a functional food because of probiotic content that are good for the digestive system. Objective: To analyze the acceptability, protein content, lipid content and microbial content of cow milk kefir compared to goat milk kefir. Method: This research is a quantitative study using CRD (Completely Randomized Design) with one factor, i.e. the difference of milk type used in the kefir. The study consisted of the kefir production stage, acceptance analysis stage, and protein, lipid and microbial content analysis stage. Result: There was no difference acceptability between cow milk kefir and goat milk kefir on the color, flavor, taste and texture parameter. There is a difference in protein content between cow milk kefir (3,40 + 0,21 %) and goat milk kefir (4,28 + 0,36 %) with p value<0,05. At the lipid content, there is a difference between cow milk kefir (3,24 + 0,03 %) and goat milk kefir (3,69 + 0,02%) with p p value<0,05. Similiarly result shown at microbial content, there is a difference between cow milk kefir (3,11x106 cfu/ml) and goat milk kefir (12,36 x106 cfu/ml) with p value<0,05. Conclusion: Cow milk kefir have a higher protein, lipid and microbial content than goat milk kefir. There is no difference in acceptability between cow milk kefir and goat milk kefir.